KEANEKARAGAMAN JENIS POHON PENYUSUN VEGETASI DI HUTAN RAWA GAMBUT PADA KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Prasetyo, Bayu Aji; Manurung, Togar Fernando; Ardian, Hafiz (JURNAL HUTAN LESTARI, 2019)
Peatland is a weatland ecosystem formed by the accumulation of organic matter on the forest floor from the debris of the vegetation above it for a long time. This process occurs because of the slow rate of decomposition compared to the rate of deposition of organic matter on the wet/inundated forest floor. This study aims to determine the vegetation species diversity found in the peat swamp forest of the area of Gunung Ambawang protected forest in Kubu Sub-District of Kubu Raya Regency. The method used in this study is a plot method with the initial determination of the plot carried out through purposive sampling then the other plots were carried out by systematic sampling. Observation of forest compositionwas made in 5 (five) observation plots, with a length of 200 m, width of each plot being 20 m and distance between plots 100 m. The research found 39 species of vegetation dominated by medang species (Litsea sp) of the Lauraceae family, which is the most common vegetation found in the peat swamp forest area in the protected forest og Gunung Ambawang.Keywords: peat swamp forest, protection forest, species diversity